HUBUNGAN ANTARA MENONTON FILM TENTANG TINDAK KEKERASAN DALAM TAYANGAN TELEVISI DENGAN AGRESIVITAS REMAJA (Studi Deskriptif Analisis Di Sma Adabiah 2 Padang) - Sriwahyuningsih, Vera (Bimbingan dan Konseling, 2014)
This research Â Â is caused by intellectual ability to educate participant that by new stimulated and affected by facility Â to school or out to scholl. This research Â for having a goal: 1) to describe an film type about forcefilness action in television display who watched by to educate participant, 2) to describe an Â aggressiveness a from who by to educate participant, 3) to correlate between look at film about forcefulness action in television display with adolescent aggressiveness. This research to shape quantitative research that to having correlation descriptive. Population in research is to educate participant all to SMA Adabiah 2 Padang education year 2012/2014 and research sample removed with utlize techniq purposive sampling which to 62 human being. Researching instrument is questionnaire for analysis often to use percentage technig and correlation. A discovery research to show that r tally the same size as Â Â Â Â Â Â Â -0,004 an r table is 0,250 df 61 at significace phase 0,05 by belief level 95%, the meaning r tally more little than r table, so that can inferredânt existed a connection which significant between look at film about forcefulness action in television display with adolescent aggressiveness.